PTU-066 Lipid Biomarker as a Diagnostic Tool in Crohn's Disease Using Metabonomic Profiling in Serum and Faeces. (17th August 2016) - Ding, NS; Sarafian, M; Misra, R; Hendy, PA; Penez, L; Holmes, E; Hart, AL
Abstract : Introduction: Inflammatory bowel disease (IBD) is influenced by environmental and genetic factors which alters the gut microbiota. The human gut microbiota is involved in the maintenance of its host physiological functions and imbalance in the microbial population and its metabolic signatures may lead to disease activity and phenotype. We aimed to investigate the variations occurring in lipid metabolism between Crohn's disease (CD) vs . controls in serum and faeces by profiling using a metabonomic approach. Methods: Serum and faeces were collected from moderate to severe Crohn's disease patients prior to commencement of anti- TNF. Sample preparation: Protein precipitation with isopropanol was implemented on serum and faeces samples and prepared by biphasic extraction.Lipid profiling: The method was performed on Waters Acquity UPLCTM combined with Waters Q-Tof PremierTM mass spectrometerData processing: OPLS-DA was carried out on the XCMS extracted intensities using SIMCA P+ v13 and Matlab.Lipids annotation was derived by searching m/z against online databases (METLIN, Lipidmaps and HMDB). Results: Multivariate analyses between healthy and CD patients were performed to characterise lipid profile differences.Significant separation was observed in both serum and faeces between the two groups (Figure 1 ). Lipid metabolism is affected in CD patients compared to healthy controls. Correlation analysis showed that several triglyceride (TG) species were significantly associated with CD. TGs with medium to long chain fatty acid length and with saturations were identified at increased levels in CD patients (Figure 2). TGs with saturated fatty acids were prominent in faeces compare to serum. Moreover, TGs found in faeces were in higher concentration than in serum. Conclusion: The metabonomic study showed profound variations in both serum and faeces of CD patients. These results highlight the association between the gut microbiota and mucosal barrier function which has downstream effect on lipid metabolism and inflammation in IBD. This metabonomic approach offers potential application in diagnosing CD. Disclosure of Interest: None Declared